Respondent-driven sampling (RDS) method: Introduction and its potential use for social psychology research - Andrian Liem; Brian J. Hall (Jurnal Psikologi Sosial, 2020)
Contrary to other non-probability sampling methods in which researchers actively recruit potential participants, respondent-driven sampling (RDS) relies on connection and trust within social networks to access hidden or hard-to-reach populations through a peer-to-peer recruitment process. These interdependency relations aligned with Indonesian communal culture. Personal network size calculation in the RDS method makes this innovative sampling method approximate random sampling methods, where findings from the sample could be generalized to the target population. Considering its superiority, the RDS method could be applied in social psychology research in Indonesia to explore current sensitive social issues among hidden or hard-to-reach Indonesian sub-populations, for instance, radical religious groups. The current article aimed to concisely describe the RDS method; discuss ethical considerations, strengths, and weaknesses of the RDS method; and outline the potential use of the RDS method in improving the contribution of social psychology research in Indonesia, for example, by advancing strategies for social intervention programs. It is followed by a brief step-by-step process to conduct a study using the RDS method.